Preparation of lignin-based composite material and application of lignin-based composite material in heavy metal ion adsorption and lignocellulose reduction catalytic degradation

The lignin-based composite material prepared by the reverse suspension method solves the problem of insufficient adsorption performance of heavy metal contaminated water treatment in the prior art, realizes the high-value utilization of industrial lignin and the effective degradation of lignocellulose, and has good Application prospects.

CN119386828APending Publication Date: 2025-02-07DALIAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411129209.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art has insufficient adsorption performance when treating heavy metal-contaminated water, and it is difficult to effectively utilize lignocellulose resources, resulting in waste of resources and environmental pollution.

Method used

The lignin-based composite material was prepared by reverse suspension method, using industrial lignin as raw material, adding additives such as sodium dodecylbenzenesulfonate, polyethylene glycol and sodium alginate, and cross-linking treatment to prepare a high adsorption process. Materials of performance. This material is not only used for heavy metal ion adsorption, but can also be prepared as a catalyst by calcination, for the reduction catalytic degradation of lignocellulose.

Benefits of technology

The high-value utilization of industrial lignin has been achieved, the adsorption efficiency of heavy metal ions has been improved, and the lignocellulose has been successfully degraded into a variety of monophenol compounds through the preparation of catalysts, solving the problems of resource waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386828A_ABST
    Figure CN119386828A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of a lignin-based composite material and application of the lignin-based composite material in adsorption of heavy metal ions in wastewater and reduction catalytic degradation of lignocellulose. The preparation process of the material comprises the following steps: dispersing lignin in an aqueous solution, stirring, adding sodium dodecyl benzene sulfonate, polyethylene glycol and a sodium alginate solution into the solution, and fully mixing. Dropwise adding into mineral oil, fully stirring, adding a cross-linking agent, and fully mixing. And washing, drying and grinding to obtain the lignin-based adsorbent which is used for adsorbing heavy metal ions. In addition, the material adsorbing the heavy metal ions is calcined to prepare a catalyst which is used for reduction catalytic degradation of lignocellulose. The lignin-based composite material is prepared from industrial waste lignin and used for heavy metal ion adsorption, after heavy metal ions are adsorbed, the lignin-based composite material is prepared into a catalyst to be used for reduction catalytic degradation of lignocellulose, high-value utilization of the lignin-based composite material is achieved, and the lignin-based composite material has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and specifically relates to the preparation of a lignin-based composite material and its application in heavy metal ion adsorption in water and reduction catalytic degradation of lignocellulose. Background Art

[0002] In recent decades, due to the sharp increase in industrial pollution, such as wastewater from smelting, electrolysis, medicine, paint, alloy, electroplating, ceramic manufacturing, etc., a large amount of heavy metal pollutants have been discharged into the environment, and global environmental heavy metal pollution has become increasingly serious. At present, the conventional treatment methods for wastewater containing heavy metal ions include chemical precipitation, biological method, ion exchange method, adsorption method and filtration method. The basic principle of these methods is to convert harmful heavy metal ions in wastewater into precipitation or other forms that are easy to handle. The adsorption method has the characteristics of high efficiency, energy saving, recyclability, environmental protection, and low cost. It has developed rapidly in recent years and has become one of the important methods for removing harmful heavy metal ions in wastewater.

[0003] Lignin is the second most abundant biopolymer on earth. It has the characteristics of large reserves, low cost and good renewability. Its surface is rich in functional groups such as phenol, hydroxyl, carbonyl, methoxyl and aldehyde, most of which can serve as adsorption sites for metal ions and some organic compounds. The pulp and paper industry produces a large amount of industrial lignin every year, which is mainly directly discharged into the natural environment or incinerated, resulting in resource waste and environmental pollution. Therefore, many studies have focused on the use of lignin-based materials as adsorbents. However, the adsorption performance of single lignin is not satisfactory, so it is necessary to modify it to increase the active sites of the adsorbent and thus improve its adsorption performance. In addition, lignin in lignocellulose has a unique aromatic structure, which can be depolymerized to generate phenolic monomers. These phenolic monomers have high potential in the synthesis of aromatic chemicals; converting lignin in agricultural, forestry and paper industry waste into high-value phenolic monomers is not only beneficial to the environment, but also more economical and efficient in the use of lignocellulose resources in biomass refining. Summary of the invention

[0004] The main purpose of the present invention is to provide a method for preparing a lignin-based composite material and its application in heavy metal ion adsorption and lignocellulose reduction catalytic degradation. The present invention uses industrial lignin as a raw material, and prepares a lignin-based composite material for heavy metal ion adsorption and lignocellulose reduction catalytic degradation by a reverse suspension method, and then applies it to heavy metal adsorption and lignocellulose reduction catalytic degradation, thereby realizing the high-value utilization of industrial lignin, which has a good adsorption effect on heavy metal ions. In addition, the material after adsorbing metal ions can be prepared into a catalyst for lignocellulose reduction catalytic degradation after calcination, which can be degraded into a variety of monophenolic compounds. Therefore, the present invention has good application prospects.

[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions:

[0006] The present invention provides a method for preparing a lignin-based composite material, which comprises the following steps:

[0007] 1) dispersing lignin in an aqueous solution and stirring;

[0008] 2) adding sodium dodecylbenzene sulfonate, polyethylene glycol and sodium alginate solution to the lignin aqueous solution obtained in step 1) and mixing thoroughly;

[0009] 3) adding the mixed solution obtained in step 2) into mineral oil and stirring thoroughly;

[0010] 4) adding a cross-linking agent to the solution obtained in step 3) and mixing thoroughly; washing with an organic solvent, drying, and grinding into powder to obtain a lignin-based composite material.

[0011] Preferably, in the aforementioned preparation method, in step 1), the lignin used is industrial lignin, including at least one of alkali lignin, prehydrolyzed lignin and lignin sulfonate.

[0012] Preferably, in the aforementioned preparation method, in step 1), the lignin concentration is 20-50 g / L, the selected lignin particles need to be sieved, and the particle diameter of the lignin is ≤0.15 mm.

[0013] Preferably, in the above-mentioned preparation method, in step 1), the stirring time of the lignin aqueous solution is ≥ 10 min, at least one of mechanical stirring or magnetic stirring is selected, the rotation speed is 300-500 r / min, and the temperature is 10-50°C.

[0014] Preferably, in the aforementioned preparation method, in step 2), the mass ratio of lignin, sodium dodecylbenzene sulfonate, polyethylene glycol in the lignin aqueous solution to sodium alginate in the sodium alginate solution is 0.5-1.0:0.1-0.4:0.1-0.4:0.03-0.09, and the concentration of the sodium alginate solution is 1-3wt%, preferably 1-2wt%; for example, the mass of lignin in the lignin aqueous solution is 0.5-1.0g, the mass of sodium dodecylbenzene sulfonate is 0.1-0.4g, the mass of polyethylene glycol is 0.2-0.5g, and the mass of sodium alginate in the sodium alginate solution is 0.03g-0.09g; the preparation method of the sodium alginate solution is: dissolving sodium alginate in water to prepare a sodium alginate solution.

[0015] Preferably, in the aforementioned preparation method, in step 2), sufficient mixing needs to be carried out under stirring conditions, the stirring time is ≥ 10 min, at least one of mechanical stirring or magnetic stirring is selected, the speed is 300-500 r / min, and the temperature is 10-50°C.

[0016] Preferably, in the aforementioned preparation method, in step 3), the mineral oil selected is liquid paraffin, the volume ratio of the mixed solution obtained in step 2) to the liquid paraffin is 1:2 to 1:5, and the relative density of the liquid paraffin is 0.83 to 0.86.

[0017] Preferably, in the aforementioned preparation method, in step 3), the mixed solution in step 2) is slowly added dropwise to the liquid paraffin under stirring conditions, at least one of mechanical stirring or magnetic stirring is selected, the speed is 500-800 r / min, the stirring time is ≥20 min, and the temperature is 10-50° C. Further, the slow addition is dropwise addition.

[0018] Preferably, in the aforementioned preparation method, in step 4), the cross-linking agent selected is one of epichlorohydrin or acrylic acid, and the volume ratio of the solution obtained in step 3) to the cross-linking agent is 30:3 to 36:3.

[0019] Preferably, in the aforementioned preparation method, in step 4), sufficient mixing needs to be carried out under stirring conditions, the stirring time is ≥ 20 min, at least one of mechanical stirring or magnetic stirring is selected, the rotation speed is 500-800 r / min, and the temperature is 10-50°C.

[0020] Preferably, in the above-mentioned preparation method, in step 4), a cross-linking agent is added to step 3) and mixed thoroughly, and then filtered, and the obtained solid is washed with an organic solvent, dried and ground into powder to obtain a lignin-based composite material.

[0021] Preferably, in the aforementioned preparation method, in step 4), the organic solvents selected for washing are petroleum ether and ethanol, the volume ratio of ethanol to petroleum ether is 1:1, and petroleum ether and ethanol are washed alternately. Further, the number of times of the alternating washing is 3 to 5 times.

[0022] Preferably, in the aforementioned preparation method, in step 4), the drying temperature is 60-80° C., and the grinding particle size needs to be ≤0.15 mm.

[0023] The invention also relates to protecting the lignin-based composite material prepared by the method.

[0024] The present invention also provides the use of the lignin-based composite material in the adsorption of heavy metal ions in water and the reduction catalytic degradation of β-O-4' dimer model compounds or lignocellulose.

[0025] Preferably, in the aforementioned application of heavy metal ion adsorption in water, at least one of lead and copper ions is selected for adsorption, the lead ions come from at least one of lead nitrate, lead sulfate and lead chloride, and the copper ions come from at least one of copper nitrate, copper sulfate or copper chloride.

[0026] Preferably, in the aforementioned application of heavy metal ion adsorption in water, the pH value of the heavy metal ion solution is 1-5, and HCl or NaOH solution can be used to adjust the pH.

[0027] Preferably, in the aforementioned application of heavy metal ion adsorption in water, the lead ion concentration in the water is 50-800 mg / L, the copper ion concentration is 100-1200 mg / L, and the concentration of the lignin-based composite material is 0.3-1.0 g / L (preferably 0.6 g / L).

[0028] Preferably, in the aforementioned application of heavy metal ion adsorption in water, the lignin-based composite material is added to the heavy metal ion aqueous solution and mixed, and adsorbed in a shaker at 20-40°C and 100-180rpm for 1-120min to obtain the lignin-based composite material after adsorbing the heavy metal ions; after the adsorption is completed, it is filtered with a 0.22-0.45um water filter membrane, and the residual concentration after adsorption is determined by a UV-visible photometer.

[0029] Preferably, in the application of β-O-4′ dimer model compound or lignocellulose reduction catalytic degradation, the lignin-based composite material after adsorbing heavy metal ions is calcined in a tubular furnace and then ground into powder to obtain a calcined lignin-based composite material, which is used as a catalyst for β-O-4′ dimer model compound or lignocellulose reduction catalytic degradation. Furthermore, the lignin-based composite material after adsorbing heavy metal ions is dried and then ground before being calcined in a tubular furnace.

[0030] Preferably, in the application of β-O-4′ dimer model compound or lignocellulose reduction catalytic degradation, the tubular furnace calcination temperature is 300-500° C., the gas environment is air or nitrogen, and the calcination time is 2-3 hours.

[0031] Preferably, in the application of the β-O-4′ dimer model compound or the reduction catalytic degradation of lignocellulose, the lignocellulose selected is at least one of poplar wood powder, pine wood powder or birch wood powder.

[0032] Preferably, in the application of β-O-4′ dimer model compound or cellulose reduction catalytic degradation, the prepared catalyst and β-O-4′ dimer model compound or cellulose are dispersed in an organic solvent, then added to the lining of the reactor, and a high temperature and high pressure reaction is carried out under hydrogen conditions.

[0033] Preferably, in the application of β-O-4′ dimer model compound or lignocellulose reduction catalytic degradation, the organic solvent is one of methanol, ethanol, and propanol; the ratio of catalyst, β-O-4′ dimer model compound or lignocellulose and organic solvent is: 10-40 mg: 40-70 mg: 5-20 mL (preferably 30 mg: 50 mg: 10 mL), the hydrogen pressure is 3-4 MPa, the temperature is 200-300° C., and the reaction time is 2-4 h.

[0034] By means of the above technical solution, the present invention has at least the following advantages:

[0035] 1) The raw material used in the present invention is industrial lignin, a by-product of the pulping and papermaking process, which has the characteristics of large reserves, low cost, good renewability, etc., which greatly reduces the production cost of the adsorbent material.

[0036] 2) The lignin-based adsorption material prepared by the present invention has abundant adsorption active sites, has a strong adsorption capacity for heavy metal ions, and can remove heavy metal ions in wastewater more quickly.

[0037] 3) The present invention functionalizes and reuses the material after adsorbing heavy metal ions to prepare a catalyst for the reduction catalytic degradation of lignocellulose, providing a new idea for the reuse of waste adsorbent materials.

[0038] 4) The preparation technology of the present invention is simple to operate, energy-saving and environmentally friendly, has excellent performance, and is easy to realize industrial production.

[0039] 5) This experiment is the first to apply lignin-based composite materials to heavy metal ion adsorption and cellulose reduction catalytic degradation, realizing the multi-polar utilization of industrial waste lignin and providing a new way for its high-value utilization. Therefore, it has good application prospects.

[0040] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a schematic diagram of the process of using the lignin-based composite material of the present invention for adsorbing metal ions and reducing and catalyzing the degradation of lignocellulose.

[0042] Figure 2 This is a SEM image of the lignin-based composite material prepared in Example 1 of the present invention.

[0043] Figure 3 It is the infrared spectrum of the lignin-based composite material and lignin prepared in Example 1 of the present invention.

[0044] Figure 4 This is a study on the lead and copper adsorption performance of the lignin-based composite materials of Examples 2 to 3 of the present invention under different pH conditions.

[0045] Figure 5 This is a study on the adsorption performance of lead and copper by the lignin-based composite materials of Examples 2 to 3 of the present invention under different concentration conditions.

[0046] Figure 6 This is a study on the lead and copper adsorption performance of the lignin-based composite materials of Examples 2 to 3 of the present invention under different time conditions.

[0047] Figure 7 The lignin-based composite material prepared in Example 1 of the present invention and the adsorption of Pb 2+ The lignin-based composite materials after adsorption of lead ions and adsorption of Cu 2+ The XPS overall spectrum of the lignin-based composite material after adsorbing lead ions.

[0048] Figure 8 Example 4 of the present invention adsorbs Cu 2+ SEM image of the prepared lignin-based composite catalyst.

[0049] Fig. 9 Example 4 of the present invention adsorbs Cu 2+ EDS image of HAADF-STEM of the prepared lignin-based composite catalyst.

[0050] Fig.10 Example 4 of the present invention adsorbs Cu 2+ XRD pattern of the prepared lignin-based composite catalyst.

[0051] Fig.11 This is a gel permeation chromatogram of Example 6 of the present invention before and after the lignin-based composite material catalyst is reduced and catalyzed to degrade poplar wood powder.

[0052] Fig.12 This is a gas chromatogram of the reduction catalytic degradation of a dimer model substance by the lignin-based composite material catalyst of Example 5 of the present invention.

[0053] Fig.13 This is a gas chromatogram of reduction catalytic degradation of poplar wood powder by the lignin-based composite material catalyst in Example 6 of the present invention. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with embodiments and drawings, but the protection scope of the present invention is not limited by the specific implementation methods.

[0055] Example 1

[0056] A method for preparing a lignin-based composite material comprises the following steps:

[0057] 1) 0.8 g of industrial alkali lignin (Shandong Longli Biotechnology Co., Ltd.) was dispersed in 20 mL of deionized water and stirred in a magnetic stirrer at a speed of 500 r / min, a temperature of room temperature, and a stirring time of 10 min;

[0058] 2) Add 0.16 g of polyethylene glycol, 0.3 g of sodium dodecylbenzene sulfonate and 30 mL of a 1.5 wt % sodium alginate aqueous solution to the solution in step 1) in sequence, and continue stirring for 10 min under the above conditions to allow the solution to be fully mixed.

[0059] 3) adding the mixed solution of step 2) dropwise into 120 mL of liquid paraffin, the dropping process is carried out under stirring conditions, the speed is 800 r / min, the temperature is room temperature, and the stirring time is 30 min;

[0060] 4) Add 15 mL of cross-linking agent-epichlorohydrin to the solution in step 3) and stir well to mix. The reaction conditions are the same as in step 3);

[0061] 5) Use a Buchner funnel to filter the mixed solution of step 4), wash with petroleum ether and then with ethanol as a first wash, wash 3 to 5 times in the above order until the solution becomes clear, then take out the solid and place it in a 60°C oven to dry for 12 hours.

[0062] 6) The solid obtained in step 5) was granulated in a mortar with a particle size of ≤ 0.15 mm to obtain a lignin-based adsorbent, denoted as LM.

[0063] Example 2

[0064] Using the lignin-based adsorbent (LM) prepared in Example 1, an experiment on the adsorption of lead ions in water was carried out, which included the following steps:

[0065] 1) Take 50 ml of a 200 mg / L lead ion solution and place it in a 100 mL conical flask. Adjust the pH to 1, 2, 3, 4, and 5 with 1 M HCl and 1 M NaOH solution, then add 30 mg LM in sequence and place it in a constant temperature shaker (25°C, 180 r / min, 2 h). After filtering the solution with a 0.22 um water filter membrane, use a UV-visible photometer to detect the residual concentration and calculate the adsorption amount;

[0066] 2) Take 50 mL of lead ion solution with pH = 4 and concentration gradient of 50 mg / L, 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, 700 mg / L, and 800 mg / L respectively in a 100 mL conical flask, then add 30 mg LM in sequence, and place in a constant temperature shaker (25°C, 180 r / min, 2h). After filtering the solution with a 0.22 um water filter membrane, use a UV-visible photometer to detect the residual concentration and then calculate the adsorption amount;

[0067] 3) Take 50 mL of a lead ion solution with a pH of 4 and a concentration of 200 mg / L and place it in a 100 mL conical flask, then add 30 mg of LM in sequence and place it in a constant temperature shaker (25°C, 180 r / min). When the reaction time is 30 s, 1 min, 2 min, 5 min, 10 min, 20 min, and 30 min, respectively, the solution is filtered with a 0.22 um water filter membrane and the residual concentration is detected with a UV-visible photometer to calculate the adsorption amount.

[0068] The lignin-based composite material after adsorbing lead ions is prepared by using the lignin-based adsorbent (LM) prepared in Example 1, comprising the following steps:

[0069] Take 50mL of a lead ion solution with a pH of 4 and a concentration of 200mg / L and place it in a 100mL conical flask, then add 30mgLM in sequence, and place it in a constant temperature shaker (25℃, 180r / min, 20min). The mixed solution after adsorbing copper ions is vacuum filtered through a sand core funnel for solid-liquid separation. The solid adsorbent with copper ions is placed in an oven and dried at 60℃ for 12h, and then fully ground into particles with a mortar and pestle with a particle size of ≤0.15mm to obtain a lignin-based composite material after adsorbing lead ions.

[0070] Example 3

[0071] Using the lignin-based adsorbent (LM) prepared in Example 1, an experiment for adsorption of copper ions in water was carried out, comprising the following steps:

[0072] 1) Take 50mL of 600mg / L copper ion solution and place it in a 100mL conical flask. Adjust the pH value to 1, 2, 3, 4, and 5 with 1M HCl and 1MNaOH solution, then add 30mg LM in sequence and place it in a constant temperature shaker (25℃, 180r / min, 2h). After filtering the solution with 0.22um water system, use a UV-visible photometer to detect the residual concentration and calculate the adsorption amount;

[0073] 2) Take 50 mL of copper ion solution with pH = 4 and concentration gradient of 100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L, 600 mg / L, 800 mg / L, 1000 mg / L, and 1200 mg / L in a 100 mL conical flask, then add 30 mg of LM in sequence and place in a constant temperature shaker (25°C, 180 r / min, 2h). After filtering the solution with a 0.22 um water filter membrane, use a UV-visible photometer to detect the residual concentration and calculate the adsorption amount;

[0074] 3) Take 50 mL of copper ion solution with pH=4 and concentration of 600 mg / L in a 100 mL conical flask, add 30 mg LM in turn, and place in a constant temperature shaker (25°C, 180 r / min). When the reaction time is 1 min, 2 min, 5 min, 10 min, 20 min, and 30 min, the solution is filtered with a 0.22 um water filter membrane and the residual concentration is detected by a UV-visible photometer to calculate the adsorption amount.

[0075] The lignin-based composite material after adsorbing copper ions is prepared by using the lignin-based adsorbent (LM) prepared in Example 1, comprising the following steps:

[0076] Take 50mL of copper ion solution with pH = 4 and concentration of 600mg / L and place it in a 100mL conical flask, then add 30mgLM in sequence, and place it in a constant temperature shaker (25℃, 180r / min, 20min). The mixed solution after adsorbing copper ions is vacuum filtered through a sand core funnel for solid-liquid separation. The solid adsorbent with copper ions is placed in an oven and dried at 60℃ for 12h, and then fully ground into particles with a mortar and pestle with a particle size of ≤0.15mm to obtain a lignin-based composite material after adsorbing copper ions.

[0077] Example 4

[0078] The lignin-based composite material after adsorbing copper ions prepared in Example 3 is used to prepare a catalyst for reduction catalytic degradation of lignocellulose, comprising the following steps:

[0079] The lignin-based composite material after adsorbing copper ions was placed in a tubular furnace and calcined at 400°C in an air environment for 2 hours. The calcined particles became blocks, which were then simply ground into particles to prepare a catalyst for the reduction catalytic degradation of cellulose, recorded as CuO / C catalyst.

[0080] Example 5

[0081] The catalytic hydrogenolysis experiment of the β-O-4′ dimer model compound using the lignocellulose reduction catalytic degradation catalyst (CuO / C catalyst) obtained in Example 4 comprises the following steps:

[0082] 1) 25 mg of the β-O-4′ dimer model compound was dissolved in 10 ml of methanol and then mixed with 30 mg of CuO / C catalyst at 240° C. for 4 h in a 50 mL high temperature and high pressure reactor under 3 MPa H 2 gas flow.

[0083] 2) After the reaction in step 1), the reactor was gradually cooled to room temperature and the pressure was carefully reduced. A sand core funnel was used to vacuum filter and separate the solid-liquid mixture. The filtered solution was concentrated to an oily substance using a rotary distillation device set at 60°C.

[0084] 3) The oily substance obtained in step 2) was dissolved in 5 mL of dichloromethane, and after being fully dissolved, it was identified and quantified by GC-MS and GC.

[0085] Example 6

[0086] The reduction catalytic degradation experiment of poplar wood powder using the lignocellulose reduction catalytic degradation catalyst (CuO / C catalyst) obtained in Example 4 comprises the following steps:

[0087] 1) 50 mg of poplar wood powder was dissolved in 10 ml of methanol and then mixed with 30 mg of CuO / C catalyst in a 50 mL high temperature and high pressure reactor under 3 MPa H2 gas flow at 240°C for 4 h.

[0088] 2) After the reaction in step 1), the reactor was gradually cooled to room temperature and the pressure was carefully reduced. A sand core funnel was used to vacuum filter and separate the solid-liquid mixture. The filtered solution was concentrated to an oily substance using a rotary distillation device set at 60°C.

[0089] 3) The oily substance obtained in step 2) was dissolved in 5 mL of dichloromethane, and after being fully dissolved, it was identified and quantified by GC-MS and GC.

[0090] 4) The oily substance obtained in step 2) and poplar wood powder were respectively dissolved in 1 ml of tetrahydrofuran, and after being fully dissolved, their molecular weights were measured by GPC.

[0091] Figure 2 This is a SEM image of the lignin-based composite material prepared in Example 1 of the present invention. From the image, it can be seen that the lignin-based composite material presents a smooth cross-linked fibrous morphology.

[0092] Figure 3 The infrared spectra of the lignin-based composite material and lignin prepared in Example 1 of the present invention are shown in FIG. 1. Compared with industrial lignin, LM has a-1 The hydroxyl stretching vibration peak at 1604 cm-1 is significantly enhanced, indicating that the hydroxyl content increases and the adsorption active sites increase. -1 and 1364cm -1 The stretching vibration peak at 907 cm-1 is significantly enhanced, indicating that the lignin content is increased. -1 and 755cm -1 The stretching vibration peak of the epoxy group was observed, which further proved the successful preparation of the cross-linked modified lignin-based composites.

[0093] Figure 4 This is a study on the adsorption performance of lead and copper by the lignin-based composite materials of Examples 2 to 3 of the present invention under different pH conditions. From the adsorption amount, it can be seen that the lignin-based composite materials have a good adsorption performance on Pb 2+ and Cu 2+ The adsorption amount increases rapidly with the increase of pH value, tends to be stable at pH=4, and tends to be saturated at pH=5.

[0094] Figure 5 This is a study on the adsorption performance of lead and copper by the lignin-based composite materials of Examples 2 to 3 of the present invention under different concentration conditions. 2+ and Cu 2+ The adsorption amount increased rapidly with the increase of concentration and reached saturation when the initial concentration reached 200 mg / L and 600 mg / L respectively.

[0095] Figure 6 This is a study on the adsorption performance of lead and copper by the lignin-based composite materials of Examples 2 to 3 of the present invention under different time conditions. The lignin-based composite materials rapidly adsorbed Pb within 5 minutes. 2+ and Cu 2+ , and reached saturation after 10 min, showing its rapid adsorption ability for metal ions.

[0096] Figure 7 The lignin-based composite material prepared in Example 1 of the present invention and the lignin-based composite material adsorbed by Example 2 are 2+ The lignin-based composite material after adsorbing lead ions obtained after (pH = 4, 200 mg / L, 20min) and the lignin-based composite material after adsorbing Cu in Example 3 2+ The XPS spectrum of the lignin-based composite material after adsorption of copper ions was obtained after (pH = 4, 600 mg / L, 20 min). It can be seen from the figure that the characteristic peaks of Pb 4f and Cu 2p appeared in the XPS spectrum, indicating that Pb 2+ and Cu 2+ Successfully absorbed.

[0097] Figure 8 Example 4 of the present invention adsorbs Cu 2+SEM image of the prepared lignin-based composite catalyst. It can be seen from the image that there are fine particles attached to the carbon surface, indicating that Cu 2+ Successful loading on carbon.

[0098] Fig. 9 Example 4 of the present invention adsorbs Cu 2+ The HAADF-STEM EDS image of the prepared lignin-based composite catalyst. From the image, it can be found that the prepared lignin-based composite catalyst group must be composed of three elements: C, O, and Cu.

[0099] Fig.10 Example 4 of the present invention adsorbs Cu 2+ XRD pattern of the prepared lignin-based composite catalyst. It can be found from the figure that by comparing with the PDF standard card, it is confirmed that the Cu in the lignin-based composite catalyst exists in the form of CuO.

[0100] Fig.11 This is a gel permeation chromatogram of the material before and after the reduction catalytic degradation of poplar wood powder by the lignin-based composite material catalyst in Example 6 of the present invention. The molecular weight of the material after the reduction catalytic degradation of poplar wood powder by the lignin-based composite material catalyst is significantly lower than that before the reduction catalytic degradation, indicating that the macromolecular lignin is successfully depolymerized into small molecular compounds.

[0101] Fig.12 This is a gas chromatogram of the hydrogenolysis of the dimer model by the lignin-based composite catalyst of Example 5 of the present invention. From the product, it can be found that the lignin-based composite catalyst can effectively break the CO bond and then reduce and catalyze the degradation of the dimer model into monophenolic compounds.

[0102] Fig.13 This is a gas chromatogram of the hydrogenolysis of poplar wood powder by the lignin-based composite material catalyst of Example 6 of the present invention. From the products, it can be found that the lignin-based composite material catalyst can effectively reduce and catalyze the degradation of the dimer model into a variety of monophenolic compounds.

[0103] The above embodiments are preferred implementations of the present invention, but the implementations of the present invention are not limited to the above embodiments.

Claims

1. A method for preparing a lignin-based composite material, characterized in that: It includes the following steps: 1) dispersing lignin in an aqueous solution and stirring; 2) adding sodium dodecylbenzene sulfonate, polyethylene glycol and sodium alginate solution to the lignin aqueous solution obtained in step 1) and mixing thoroughly; 3) adding the mixed solution obtained in step 2) into mineral oil and stirring thoroughly; 4) adding a cross-linking agent to the solution obtained in step 3) and mixing thoroughly; washing with an organic solvent, drying, and grinding into powder to obtain a lignin-based composite material.

2. The preparation method according to claim 1, characterized in that: In step 1), the lignin used is industrial lignin, including at least one of alkali lignin, prehydrolyzed lignin or lignin sulfonate; the particle diameter of the lignin is ≤0.15mm; the concentration of the lignin is 20-50g / L; the stirring time of the lignin aqueous solution is ≥10min, at least one of mechanical stirring or magnetic stirring is selected, the rotation speed is 300-500r / min, and the temperature is 10-50°C.

3. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of lignin, sodium dodecylbenzene sulfonate, polyethylene glycol in the lignin aqueous solution to sodium alginate in the sodium alginate solution is 0.5-1.0:0.1-0.4:0.1-0.4:0.03-0.09, and the concentration of the sodium alginate solution is 1-3wt%; the mixing is carried out under stirring conditions, the stirring time is ≥10min, at least one of mechanical stirring or magnetic stirring is selected, the rotation speed is 300-500r / min, and the temperature is 10-50°C.

4. The preparation method according to claim 1, characterized in that: In step 3), the mineral oil used is liquid paraffin with a relative density of 0.83 to 0.86, and the volume ratio of the mixed solution obtained in step 2) to the liquid paraffin is 1:2 to 1:5; the mixed solution obtained in step 2) is added dropwise to the mineral oil; at least one of mechanical stirring or magnetic stirring is selected, the rotation speed is 500 to 800 r / min, the stirring time is ≥20 min, and the temperature is 10 to 50°C.

5. The preparation method according to claim 1, characterized in that: The cross-linking agent used in step 4) is one of epichlorohydrin or acrylic acid, and the volume ratio of the solution obtained in step 3) to the cross-linking agent is 30:3 to 36:3; the mixing is carried out under stirring conditions, the stirring time is ≥20min, at least one of mechanical stirring or magnetic stirring is selected, the rotation speed is 500 to 800r / min, and the temperature is 10 to 50°C; the organic solvents used for washing are petroleum ether and ethanol, and the petroleum ether and ethanol are washed alternately; the drying temperature is 60 to 80°C; the particle size of the ground powder is ≤0.15mm.

6. A lignin-based composite material, characterized in that: It is prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the wood lignin-based composite material according to claim 6 in the adsorption of heavy metal ions of pollutants in water and the reduction and catalytic degradation of β-O-4' dimer model compounds or lignocellulose.

8. The use according to claim 7, characterized in that: The heavy metal includes at least one of lead and copper, and the wood cellulose includes at least one of poplar wood powder, pine wood powder or eucalyptus wood powder.

9. The use according to claim 7, characterized in that: The lignin-based composite material after heavy metal adsorption is calcined and then ground into powder to obtain a calcined lignin-based composite material, which is used as a catalyst for the reduction catalytic degradation of β-O-4' dimer model compounds or lignocellulose.

10. The use according to claim 9, characterized in that: The lignin-based composite material after adsorbing heavy metal ions is dried and then ground before being calcined in a tubular furnace; the calcination temperature is 300-500° C., the environment is air or nitrogen, and the time is 2-3 hours.